Can Gamification Foster Trust-Building in Human-Robot Collaboration? An Experiment in Virtual Reality - Riar, Marc; Weber, Mareike; Ebert, Jens; Morschheuser, Benedikt (2025)
With the increasing deployment of robots to support humans in various activities, a crucial factor that has surfaced as a precondition for successful human-robot interaction (HRI) is the human’s level of trust in the robotic companion. A phenomenon that has recently shifted into the foreground for its potential to influence cognitive and affective dimensions in humans is gamification. However, there is a dearth of knowledge whether and how gamification can be employed to effectively cultivate trust in HRI. The present study investigates and compares the effects of three design interventions (i.e., non-gamified vs. gameful design vs. playful design) on cognitive and affective trust between humans and an autonomous mobile collaborative robot (cobot) in a virtual reality (VR) training experiment. The results reveal that affective trust and specific trust antecedents (i.e., a robot’s likability and perceived intelligence) are most significantly developed via playful design, revealing the importance of incorporating playful elements into a robot’s appearance, demeanor, and interaction to establish an emotional connection and trust in HRI.<br